Agency non umana in un Medioevo postumano: la teoria di Biagio Pelacani sulla generazione spontanea dell’umano dalla materia [Non-human agency in posthuman Middle Ages: Biagio Pelacani's theory on the spontaneous generation of humans from matter] - Orsola Rignani (Open Journal of Humanities, 2020)
I propose to investigate the posthuman idea of non-human agency by creating a contact zone with the thought of the Thirteenth Century philosopher Biagio Pelacani. In a ‘medieval posthumanist’ style, I put in place a creative dialogue with Pelacani on the non-human agency in order to attract critical attention on the relevance, implications, historicity of the posthuman idea of non-human agency. In such a perspective I grasp in Pelacani an idea of material agency that is embodied in a metaphysical-cosmological doctrine according to which there’s an a unique material living animated principle from whose power all that is, including the human with its intellect, is taken from (human spontaneous generation from matter). In this idea of material agency with its attempt to articulate the boundaries of the human within a vibrant matter it therefore seems to me that I can read a significant trigger for the posthuman idea of agency in its implications of destabilizing the notion of human exceptionality.